Does the Disease of the Person Receiving Care Affect the Emotional State of Non-professional Caregivers? - Otero, Patricia; Torres, Ángela J.; Vázquez, Fernando L.; Blanco, Vanessa; Ferraces, María J.; Díaz, Olga (Frontiers in Psychology, 2019)
Research on mental health of non-professional caregivers has focused on caregivers of people with specific diseases, especially dementia. Less is known about caregivers of people with other diseases. The aims of this study were (a) to determine the caregivers’ emotional state in a random sample of caregivers of people in situations of dependency, (b) to analyze the association between each disease of the care-recipient (a variety of 23 diseases included in the International Classification of Diseases) and the emotional state of the caregiver, and (c) based on the theoretical model, to analyze the relationship of the different study variables in the appearance of the emotional distress of the caregiver. A sample of 491 non-professional caregivers was selected randomly (89.0% women, average age 55.3 years). Trained psychologists collected sociodemographic and care-related characteristics and evaluated the global emotional distress, somatic symptoms, anxiety-insomnia, social dysfunction, depression, probable mental disorder case, self-esteem and social support. It was found that (a) the caregivers showed moderate emotional distress, and 33.8% presented a probable mental disorder. (b) Caring for a care-recipient with cat's cry syndrome or epilepsy was related to suffering from social dysfunction, and caring for a care-recipient with autism was related to having a probable mental health case. (c) Social support mediated the relationship between social class, daily hours of care, monthly family income, self-esteem and global emotional distress. There is an important impact on the emotional state of the caregivers. This impact was similar in caregivers of care-recipients with different diseases, except in caregivers caring for a care-recipient with cat's cry syndrome or epilepsy (related to social dysfunction), and in caregivers caring for a care-recipient with autism (related to having a probable mental health case).